2021
DOI: 10.4103/meajo.meajo_358_20
|View full text |Cite
|
Sign up to set email alerts
|

A case–cohort study of exfoliation risk factors and literature review

Abstract: The purpose of the study is to evaluate the risk factors associated with exfoliation in a case-cohort setting and literature review. This single-center, prospective, case-cohort study was carried out from January 2010 to April 2020 on patients operated for cataract surgery by a single surgeon in Lebanon. Forty-nine consecutive patients with exfoliation syndrome (XFS) and 62 consecutive control patients were identified and further investigated for selected systemic (diabetes mellitus, systemic hypertension, ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 115 publications
(205 reference statements)
0
4
0
Order By: Relevance
“…Although the mechanism is not clear, long axial length can be considered a predisposing factor for the development of early-onset XFS, while intraocular surgery serves as an environmental factor. Few case-control studies have reported the association between long axial length and XFS 9,11 , which makes it difficult to interpret our findings. This could be attributed to the fact that young patients with this condition have rarely been included in previous studies.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Although the mechanism is not clear, long axial length can be considered a predisposing factor for the development of early-onset XFS, while intraocular surgery serves as an environmental factor. Few case-control studies have reported the association between long axial length and XFS 9,11 , which makes it difficult to interpret our findings. This could be attributed to the fact that young patients with this condition have rarely been included in previous studies.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, based on aqueous humour (AH) analysis from XFS eyes, transforming growth factor beta-1 (TGF-β1), pro-inflammatory cytokines, and oxidative stress have also been suggested to play an important role in the pathogenesis of XFS [6][7][8] .Considering that the prevalence of XFS increases with age and that most cases of XFS develop in individuals aged over 60 years [5][6][7][8][9] , increasing age is a definite risk factor for the development of XFS 5,9 . Interestingly, however, XFS may develop at a young age in some cases 10,11 . We believe that investigating the clinical features of patients with early-onset XFS and the associated risk factors can provide insights into the pathogenesis of XFS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Several studies on the PEXS estimated a 5 to 20% prevalence in an aged population regardless of geographical features ( 26 ). Specifically, PEXS is common in individuals >50 years, with its incidence increasing with age.…”
Section: Incidence Of Pexsmentioning
confidence: 99%